THE CHALLENGE OF EMBRACING HUMAN RIGHTS AS A FUNDAMENTAL ELEMENT OF CONSTITUTIONALISM: A STUDY OF INDONESIA’S CONSTITUTIONAL JOURNEY (Lex localis - Journal of Local Self-Government, 2025)
The adoption of human rights in the constitution is crucial in enhancing constitutionalism. In accordance with social contract theory, the people are the ultimate source of authority, from which governmental power is derived, and the primary tasks of the government encompass the protection of human rights. In any event, there are some particular constitutions are referred to ‘constitution without constitutionalism’ or as ‘sham constitutionalism’, both of which indicate the existence or absence of the rule of law, separation of powers, and the protection of human rights. These types of constitution may likewise contribute to the establishment of authoritarianism. This phenomenon generates a political pattern, known as ‘political paradox’. In the context of Indonesia’s constitutional journey, this pattern illustrates that despite the constitutional reform in 1999-2002 adopting human rights principles, the acceptance by the people continues to encounter significant challenge. The underlying cause is the impact of the political paradox, which encompasses political dynamics, cultural perspective, and background history of constitution drafting. This paradox entraps public’s perception regarding the value of democracy and human rights. They continue to posit these values as external construct that do not align with genuine Indonesian values. Accordingly, it is crucial to elevate critical thinking in the analysis of history of Indonesian constitution to ensure the correct and comprehensive understanding, thereby enabling the incorporation of democratic ideal and human rights principles within the structure of ‘our law’ acceptance, as a core component of constitutionalism.